Channel-aware routing and priority-aware multi-channel scheduling for WSN-based smart grid applications. (August 2016) - Yigit, Melike; Gungor, V. Cagri; Fadel, Etimad; Nassef, Laila; Akkari, Nadine; Akyildiz, Ian F.
Abstract: Wireless Sensor Networks (WSNs) are one of the most promising solutions for smart grid applications due to advantages, such as their low-cost, different functionalities, and successful adoption to smart grid environments. However, providing quality of service (QoS) requirements of smart grid applications with WSNs is difficult because of the power constraints of sensor nodes and harsh smart grid channel conditions, such as RF interference, noise, multi-path fading and node contentions. To address these communication challenges, in this paper link-quality-aware routing algorithm (LQ-CMST) as well as the priority and channel-aware multi-channel (PCA-MC) scheduling algorithm have been proposed for smart grid applications. Furthermore, the effect of different modulation and encoding schemes on the performance of the proposed algorithms has been evaluated under harsh smart grid channel conditions. Comparative performance evaluations through extensive simulations show that the proposed algorithms significantly reduce communication delay and the choice of encoding and modulation schemes is critical to meet the requirements of envisioned smart grid applications.